Application of microbial mineralization technology for marine concrete crack repair: A review. (15th June 2023) - Fan, Qi; Fan, Liang; Quach, Wai-Meng; Zhang, Ruiyong; Duan, Jizhou; Sand, Wolfgang
Abstract: Microbially induced calcium carbonate precipitation (MICP) is an emerging biotechnology with a wide range of potential applications in structural repair. Compared to conventional concrete repair methods, MICP is economically feasible and sustainable. The restoration effects of MICP have been proved in the laboratory. However, due to the harsh marine environment, this technology has not been widely applied to marine concrete restoration yet. This paper mainly reviews the mineralization mechanisms of five common types of mineralizing bacteria and analyzes the effects of temperature, pH, and medium components on bacterial reproduction and calcium carbonate precipitation. Then, four strategies for concrete crack repair are introduced, and restoration effects are evaluated according to the strength and durability of repaired specimens. Next, the effects of marine environment and ions in seawater on the bacterial reproduction, yields of calcium carbonate, and crack restoration are explored. The potential adverse effects of the MICP process on the environment and reinforcement corrosion are discussed as well. Finally, the challenges and suggestions are put forward to promote the application of MICP in marine concrete restoration. Graphical abstract: Image 1 Highlights: Mineralization mechanisms of different bacteria are reviewed. Environmental effects on bacterial reproduction and calcium carbonate yield are compared. Advantages and limitations of the different repair strategies are evaluated. Challenges of MICP application for marine concrete restoration are discussed.